Assessing cognitive flexibility in humans and rhesus macaques with visual motion and neutral distractors - Yurt, Pinar; Calapai, Antonino; Mundry, Roger; Treue, Stefan (Frontiers in Psychology, 2022)
Cognitive flexibility is the ability of an individual to make behavioral adjustments in response to internal and/or external changes. While it has been reported in a wide variety of species, established paradigms to assess cognitive flexibility vary dramatically across species, making systematic comparisons difficult to interpret, especially between humans and non-human animals. We developed a comprehensive computer-based paradigm to assess cognitive flexibility in humans and non-human primates alike and tested captive rhesus macaques and human participants. Our paradigm 1) uses the classical reversal learning structure in combination with a set-shifting approach (4 stimuli and 3 rules) to assess flexibility at various levels; 2) it employs the use of motion as one of three possible contextual rules; 3) it comprises elements that allow a foraging-like and random interaction i.e., instances where the animals operate the task without following a strategy, to potentially minimize frustration in favor of a more positive engagement. Prior to testing, all participants completed an automated training procedure to learn the few basic rules of the task. We show that motion can be used as a feature dimension (in addition to commonly used shape and color) for cognitive testing in general and to assess cognitive flexibility in particular. Due to the way motion is processed in the primate brain, we argue that this dimension is an ideal candidate in situations where a non-binary rule set is needed and where participants might not be able to fully grasp other visual information of the stimulus (e.g., quantity in Wisconsin Card Sorting Test). All participants in our experiment flexibly shifted to and from motion-based rules as well as color- and shape-based rules, but did so with different efficiencies. We designed an algorithm that would help animals when stuck, running on the background of a task that employed four simultaneous stimuli, that rewarded exploration and tolerated random interaction. Overall, we believe that with such approach it is possible to deepen the understanding of the evolution of cognitive flexibility in primates, as well as developing more efficient tools to diagnose and treat for various executive function deficits.